Racial ideology, system justification, and just world belief in African Americans - Johnson, Sydney Katherine; Thomas, Kendra (Frontiers in Psychology, 2023)
Just world belief and system justification have previously been proposed to explain actions and beliefs of disadvantaged groups, but rarely together and never simultaneously in participants of color. A necessary expansion of work in this area is among African-American participants with differing views of race and how those views influence justice perceptions. Racial ideologies, used in African-American racial identity research, were studied as possible predictors of belief in a just world and system justification scores. The four racial ideologies examined in this study are assimilationist, humanist, nationalist, and oppressed minority. The current study examines belief in a just world and system justification as predicted by racial ideology. Participants (n = 261) responded to an online survey containing racial ideology items from the Multidimensional Model of Racial Identity (MMRI), the General and Personal Just World Scales, and the General System Justification Survey. Hierarchical linear regression was conducted, finding that nationalist ideology significantly predicted system justification and general just world belief.